The daughter of man - Sysko, L. J. (Miller Williams Poetry Prize Series., 2023)
"The Daughter of Man, finalist for the 2023 Miller Williams Poetry Prize, follows its unorthodox heroine as she transforms from maiden to warrior-then to queen, maven, and crone-against the backdrop of suburban America. This collection confronts misogyny and violence even as it bursts with nostalgia, lust, and poignant humor"--